Cattle herding and coexistence between protected areas and their periphery : a participatory approach - (:unkn) unknown (My University, 2015)
About 15 % of the world’s terrestrial area has some kind of protected status. Human-wildlife conflicts, crops raiding, livestock predation, poaching, illegal natural resources harvesting, the list of issues taking place at the edge of African protected areas is long. These issues are wicked problems, characterized by scientific uncertainties and involve conflictive cultural values and interconnections with other problems. The constructivist approach of post-normal sciences (PNS) assumes that reality is socially constructed. Studying and addressing wicked problems therefore requires insights on local stakeholders’ perspectives. In this PhD we focused on interactions between the Sikumi Forest (SF), a Zimbabwean protected area, and the rural communities living at its periphery. More particularly, we focused on the tensions related to cattle herding practices. The situation shows characteristic of wicked problems: the difficulty to frame a precise problem; high uncertainties about the studied SES; incomplete scientific knowledge; competing cultural values; and the interconnection to other problems. In order to understand cattle-related interactions between rural communities and the protected area, we co-designed a participatory research tool taking the form of a role-playing game (RPG) enabling us to elicit cattle herding strategies. The RPG was used with naïve villagers (villagers who were note involved in the co-design). This PhD thesis shows how the use of virtual worlds allows researchers to cope with the catch-22 of wicked problems, that is that any action transforms the problem and brings us “back to the beginning”. The co-design of the research tool allows to deal with one of the major characteristics of wicked problems: uncertainties. In the participatory design of the RGP, these were collectively reframed through negotiation. Participation led to the appropriation of the co-designed object by local actors, as a result our project went bey
Keywords: African Research